The Role of Courts under a Bill of Rights: A Theory of Judicial Restraint - Kavanagh, Aileen (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
The aim of this paper is twofold. First, it provides an overview of the system of the rights-based under the UK Human Rights Act 1998, trying to show that although it is often described as a leading exemplar of ‘weak-form’ constitutional review, in reality, the UK system displays many signs of subtle strength. Second, it adopts the decision making of the English courts under this bill of human rights to elaborate a theory of judicial restraint. The upshot is that when assessing any system of constitutional review in order to determine the strength or weakness of judicial power, we need to look beyond the formal textual mechanisms to explore the doctrines and devices judges use when reviewing legislation for compliance with rights.
Keywords: Rights-based judicial review; weak-form judicial review; judicial supremacy; judicial restraint